Novel Poxin Stable cGAMP‐Derivatives Are Remarkable STING Agonists. Issue 40 (31st August 2022) - Stazzoni, Samuele; Böhmer, Daniel F. R.; Hernichel, Fabian; Özdemir, Dilara; Pappa, Aikaterini; Drexler, David; Bauernfried, Stefan; Witte, Gregor; Wagner, Mirko; Veth, Simon; Hopfner, Karl‐Peter; Hornung, Veit; et al.
Abstract: 2′, 3′‐cGAMP is a cyclic A‐ and G‐containing dinucleotide second messenger, which is formed upon cellular recognition of foreign cytosolic DNA as part of the innate immune response. The molecule binds to the adaptor protein STING, which induces an immune response characterized by the production of type I interferons and cytokines. The development of STING‐binding molecules with both agonistic as well as antagonistic properties is currently of tremendous interest to induce or enhance antitumor or antiviral immunity on the one hand, or to treat autoimmune diseases on the other hand. To escape the host innate immune recognition, some viruses encode poxin endonucleases that cleave 2′, 3′‐cGAMP. Here we report that dideoxy‐2′, 3′‐cGAMP (1 ) and analogs thereof, which lack the secondary ribose‐OH groups, form a group of poxin‐stable STING agonists. Despite their reduced affinity to STING, particularly the compound constructed from two A nucleosides, dideoxy‐2′, 3′‐cAAMP (2 ), features an unusually high antitumor response in mice. Abstract : Dideoxy‐cyclic‐dinucleotide analogs of cGAS/STING second messenger 2′, 3′‐cGAMP are prepared using a new and concise synthetic combination of phosphoramidite and phosphotriester chemistry. The dideoxy analogs are found to exhibit remarkable in cellulo and in vitro properties, are stable against degradation by poxvirus immune nucleases, and exhibit superior tumor growth control in a mouse model.